Moral judgment: What makes it unique? - Abele-Brehm, Andrea (The Routledge International Handbook of the Psychology of Morality, 2023)
Social judgments and social evaluations are the basis of our understanding and interpretation of the world. People constantly evaluate themselves, other individuals, their own groups, and other groups in society, and this is functional for guiding behavior. Moral judgments are part of the “getting along” dimension and together with friendliness-, ability-, and assertiveness-judgments they form the “Big Two” of social evaluation. The term morality can be used in quite different ways, for instance, in a descriptive versus normative sense. Descriptively, it addresses what a specific society or a specific group sees as moral. Normatively, morality refers to behaviors that ought to be performed or ought to be avoided. Moral judgments are based on values. These values may stem from religious conviction and/or from political and cultural beliefs. Depending on specific values different behaviors can be regarded as moral.<br
CRIS-Team Scopus Importer:2024-12-16